COVID-19 and hypercoagulability - Ölmez, Hasan; Tosun, Mustafa; Ünver, Edhem; Doğan, Mehmet; Arslan Işık, Nurten (The European Research Journal, 2021)
It has been observed that patients with COVID-19 infection may develop acute pulmonary embolism (APE), acute myocardial infarction, limb thrombosis, and venous and / or arterial thrombosis, including central nervous system. Thrombosis formation in COVID-19 patients can be explained by the virchow triad. Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) can directly attack vascular endothelial cells, causing excessive activation of the immune system and cytokine storm, causing thrombosis. Increased prothrombotic factors such as antiphospholipid antibodies, elevated factor VIII, high fibrinogen, circulating prothrombotic microparticles, neutrophil extracellular traps have been reported in COVID-19 infection. It has been argued that complement-mediated endothelial damage, increase in pro-inflammatory cytokines such as interleukin (IL)-1, IL-6, IL-8 and interferon-γ may be the cause of thrombosis. Autopsies of patients with COVID-19 revealed that the causes of death were pneumonia and pulmonary embolism. When monitoring COVID-19 patients, platelet, prothrombin time (PT) and activated partial thromboplastin time (aPTT), fibrinogen and D-dimer monitoring should be initiated every 1-2 days, especially in critically ill patients. High D-dimer levels are associated with high mortality; may indicate infection/sepsis, cytokine storm, and impending organ failure. Disseminated intravascular coagulation (DIC) may be seen in COVID-19 patients, but unlike DIC, fibrinogen is usually high. Clotting times and platelet counts are usually normal. Therefore, it is appropriate to use sepsis-induced coagulopathy (SIC) criteria in the follow-up of COVID-19 patients. Infected areas related to pulmonary embolism can be seen as radiological appearance. Some patients may have enlarged subsegmental pulmonary vessels. Treatment of the underlying disease is the most important treatment for all coagulopathies. Patients with venous thromboembolism, inpatient medical, surgical, and COVID-19 therapy should receive anticoagulant therapy unless there is a contraindication to anticoagulation (for example, active bleeding or severe bleeding within the previous 24 to 48 hours).